2016
DOI: 10.1186/s40249-016-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

Presence of three dengue serotypes in Ouagadougou (Burkina Faso): research and public health implications

Abstract: BackgroundThe significant malaria burden in Africa has often eclipsed other febrile illnesses. Burkina Faso’s first dengue epidemic occurred in 1925 and the most recent in 2013. Yet there is still very little known about dengue prevalence, its vector proliferation, and its poverty and equity impacts.MethodsAn exploratory cross-sectional survey was performed from December 2013 to January 2014. Six primary healthcare centers in Ouagadougou were selected based on previously reported presence of Flavivirus. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 38 publications
8
92
0
Order By: Relevance
“…In the last half century, the prevalence of the dengue virus (DENV) has increased dramatically (up to 30%) worldwide, especially in Sub‐Saharan Africa . In Sub‐Saharan Africa, dengue fever represents an added underestimated burden to an infectious disease landscape dominated by malaria . In this context, febrile illnesses, including dengue, are likely to be misdiagnosed and treated as malaria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last half century, the prevalence of the dengue virus (DENV) has increased dramatically (up to 30%) worldwide, especially in Sub‐Saharan Africa . In Sub‐Saharan Africa, dengue fever represents an added underestimated burden to an infectious disease landscape dominated by malaria . In this context, febrile illnesses, including dengue, are likely to be misdiagnosed and treated as malaria.…”
mentioning
confidence: 99%
“…The first dengue epidemic known in Burkina Faso occurred in 1925 . Since then, a significant number of cases was reported in the 1980s, in the 2000s and, more recently, during the 2013 and 2015 outbreaks . In 2016, Burkina Faso experienced another dengue outbreak.…”
mentioning
confidence: 99%
“…In 2007, DENV-1 was identified (9); another outbreak, this time involving DENV-3, occurred in Burkina Faso from October 18 to November 8, 2013 (10). From December 2013 to January 2014, outbreaks of DENV-2, DENV-3, and DENV-4 were reported in the country (11). In the recent outbreak of dengue in 2016, Eldin et al isolated DENV-2 from a traveler returning from Burkina Faso to France (12).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, yellow fever is considered as an emerging or reemerging disease of considerable importance. Furthermore, since 2000, dengue cases have been described in several West and Central Africa countries: Burkina Faso (2007, 2008, 2013–2015), Cameroon (2006), Ivory Coast (2007, 2008, 2010), Gabon (2007, 2008, 2010), Mali (2008) and Senegal (2000, 2007–2009) [3,7,8,9]. In 2009, a large outbreak of dengue fever (more than 6000 cases) occurred in the Cape Verde Islands, where dengue virus was never isolated before, leading to considering the phenomenon as a true emergence of dengue fever in Africa [10].…”
Section: Introductionmentioning
confidence: 99%
“…The first dengue fever outbreak was described in the 1980s [12] and in the following years several limited outbreaks occurred in Ouagadougou and Bobo-Dioulasso, the country’s main towns. In 2013, dengue was reported in healthcare centers of Ouagadougou [9]. For yellow fever, the survey carried out by Yaro et al [13] in the Southwestern part of Burkina Faso showed an increase of confirmed cases between 2003 and 2005, possibly associated with the intensification of migration between Burkina Faso and Côte d’Ivoire.…”
Section: Introductionmentioning
confidence: 99%